Plagiarism in nursing education: an integrative review. Issue 19 (20th March 2017) - Lynch, Joan; Everett, Bronwyn; Ramjan, Lucie M; Callins, Renee; Glew, Paul; Salamonson, Yenna
Abstract : Aims and objectives: To identify the prevalence and antecedents of plagiarism within nursing education and approaches to prevention and management. Background: There has been growing media attention highlighting the prevalence of plagiarism in universities, including the academic integrity of undergraduate nursing students. A breach of academic integrity among nursing students also raises further concern with the potential transfer of this dishonest behaviour to the clinical setting. Design: Integrative review. Methods: A systematic search of five electronic databases including CINAHL, MEDLINE, SCOPUS, ProQuest Nursing & Allied Health Source, and ERIC was undertaken. Only primary studies related to plagiarism and nursing students (undergraduate or postgraduate) studying at a tertiary education institution or nursing faculty were included. Both qualitative and quantitative study designs were included. Results: Twenty studies were included in this review with six key themes identified: (1) prevalence; (2) knowledge, understanding and attitudes; (3) types of plagiarism; (4) antecedents to plagiarism; (5) interventions to reduce or prevent plagiarism; and (6) the relationship between academic honesty and professional integrity. Plagiarism is common among university nursing students, with a difference in perception of this behaviour between students and academics. The review also highlighted the importance of distinguishing between inadvertent and deliberate plagiarism, with differing strategies suggested to address this behaviour. Nevertheless, interventions to reduce plagiarism have not been shown to be effective. Conclusions: The current punitive approach to plagiarism within nursing faculties has not reduced its occurrence. There is a need to promote awareness, knowledge and provide students with the appropriate referencing skills, to reduce the significant amount of inadvertent plagiarism. Relevance to clinical practice: The importance of promoting honesty and academic integrity in nursing education is highlighted. Cheating within the academic setting has been associated with dishonesty in the clinical setting, which highlights the importance of nurturing a culture of honesty and integrity at university.